Prevalence of malaria parasites among blood donors in two hospitals in Enugu metropolis, Nigeria - Samuel ThankGod Aluh; Patience Obiageli Ubachukwu; Kyrian Ikenna Onah; Gabriel Adebayo Oladepo; Chidi Ole Ukwen; Fupsin Rimamkirnde (Hematology, Transfusion and Cell Therapy)
Introduction: Screening of blood donors for malaria parasites as recommended by the World Health Organization (WHO) is currently not included in the protocols and procedures for pre-screening blood donors of many private and public health facilities in Nigeria. Methods: A cross-sectional study was conducted of voluntary, family, and remunerated blood donors in two hospitals in the Enugu metropolis. A well-structured questionnaire was used to collect demographics and blood donation history data. Five milliliters of blood were collected from each blood donor, of which 2 mL were used to screen for malaria parasites. Results: Three hundred and seventy-seven blood donors participated in the study with 148 (39.3 %) being malaria-positive. Most of the blood donors were in the age groups 16–25 and 26–35 years old with prevalences of 40.0 % and 44.1 %, respectively. The prevalence of malaria in both age groups was high compared to the 36–45 years age group (26.7 %). Still, the overall difference in malaria prevalence across the four age groups was not statistically significant (χ2 = 5.437; p-value = 0.142). The majority (n = 290; 76.9 %) of the donors were male, while 87 (23.1 %) were female. Although female blood donors had a higher prevalence of malaria (47.1 %) compared to male donors (36.9 %), the difference was not statistically significant (p-value = 0.057). Conclusion: The high prevalence of malaria in the studied area, suggests the need for careful screening of blood samples of blood donors for malaria parasites.